Bi nanodendrites for highly efficient electrocatalytic NO reduction to NH3 at ambient conditions. (January 2022) - Lin, Yiting; Liang, Jie; Li, Haobo; Zhang, Longcheng; Mou, Ting; Li, Tingshuai; Yue, Luchao; Ji, Yuyao; Liu, Qian; Luo, Yonglan; Li, Na; Tang, Bo; et al.
Abstract: Electrocatalytic NO reduction into value-added NH3 addresses the need for NO emission abatement and presents a sustainable alternative to the industrial Haber–Bosch process. It is however challenged by unsatisfactory conversion efficiencies due to competitive hydrogen evolution and requires highly active and selective catalysts for NO reduction reaction (NORR). In this work, we report the Bi nanodendrites (Bi NDs) with sufficient exposure of catalytic sites act as a high-efficiency NORR electrocatalyst toward selective NH3 synthesis. This catalyst attains a remarkable NH3 yield of 1194 μg h −1 mg −1 cat. and a Faradaic efficiency as high as 89.2% in neutral media, making it one of the most promising aqueous-based NORR catalysts for NO-to-NH3 conversion. Additionally, we coupled Bi NDs-loaded carbon paper into an aqueous Zn–NO battery with a Zn plate anode to provide a peak power density of 2.33 mW cm −2 and an NH3 yield of up to 84.4 μg h −1 cm −2 . NO reduction mechanism on the Bi (012) surface is further revealed and discussed with theoretical calculations. Graphical abstract: Bi nanodendrite behaves as a high-active and stable electrocatalyst for ambient NO reduction into NH3 with a yield of 1194 μg h −1 mg −1 cat. and a Faradaic efficiency as high as 89.2%. The Zn–NO battery with Bi nanodendrite as the cathode material delivers a power density of 2.33 mW cm −1 and an NH3 yield of 84.4 μg h −1  mg −1 cat. . Image 1 Highlights: Bi nanodendrite is proposed as an earth-abundant NORR electrocatalyst in neutral media. It attains a large NH3 yield (1194 μg h −1 mg −1 cat. ) and a high Faradaic efficiency (89.2%). Zn–NO battery offers a peak power density of 2.33 mW cm −2 and an NH3 yield of 84.4 μg h −1 cm −2 . NO reduction mechanism is investigated by theoretical calculations.